Peningkatan Kemampuan Analisis Siswa dalam Pembelajaran Ilmu Pengetahuan Sosial dengan Model Pengajaran Langsung Berbasis Masalah - Lanjar Pratiwi; Samsudi Samsudi; Hamdan Tri Atmaja (Jurnal Inovasi Pendidikan Dasar, 2016)
The study aims to develop and validate problem-based direct instruction model in learning of social studies and determine the effectiveness of the learning model in improving the students' analytical ability. This study employed the Research and Development (RnD) with the 4D model that being modified into the 3D model. The subjects are the fourth-grade students of Gugus Kartini Semarang elementary school. The data are collected by interview, test, observation, and questionnaire. The data analysis involves descriptive qualitative analysis, classical completeness analysis, average completeness analysis, comparative analysis, and analysis of the increase of Normalized Gain. The result of data analysis showed that the average of validator value for learning tools is 3,74. The average percentage of teacher responses is 93,1%, student responses are 90%, and teachers’ teaching skills is 91.3%. The average of students’ analytical ability is 84,53 which is above the minimum completeness criteria. Furthermore, the normalized Gain test indicated an increase in student analytical ability by 71%. Therefore, the finding of this study indicated that problem-based direct instruction model that developed have valid, effective and practical value.